PENERAPAN MESIN PENGEMBANG ADONAN DAN OVEN DENGAN KONTROL SUHU OTOMATIS PADA INDUSTRI ROTI DAN CATERING DI DESA PENGKOL KABUPATEN JEPARA - Safrizal; Sisno Riyoko; Isyfa Fuhrotun Nadhifah; Dimas Ariyanto; Alfi Nur Fachri; Muhammad Alif Najih (STKIP Citra Bakti, 2023)
Pengkol Village is the center of the catering industry in Jepara district and is growing until now. The development of the catering industry is hampered by various problems that often arise, including packaging design, markets, equipment, capital and governance (management). Most catering entrepreneurs already feel comfortable with the current conditions even though they do not know whether they are profitable or not in running a business. Problems that exist in partners require carefulness and concrete actions to solve problems according to the priority needs of partners, so that problem solving is in accordance with the targets and outputs achieved. To solve the problems faced by partners, in this community service, catering entrepreneurs will get the facilitation of a Dough Developer Machine with automatic temperature control, an oven with automatic temperature and time control, a non-stick pan which is expected to be able to develop the productivity of entrepreneurs both in producing, making packaging design and opening up market opportunities both in the Jepara region and outside the Jepara region by promoting through various social media and andorid-based sales applications